55th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2014
DOI: 10.2514/6.2014-0503
|View full text |Cite
|
Sign up to set email alerts
|

Degradation in Cellular Core Mechanical Properties due to Transverse Compression

Abstract: Manufacturing defects, which occur often in cellular cores of sandwich structures, lead to buckled cells in the core and thus to degraded constitutive core properties. Defects in the core cells may occur due to unintentional tool impacts onto the panel during manufacturing, handling processes, or defects in the manufactured core itself. The degraded constitutive properties of the core lead to local stiffness degradations of the sandwich panel, which in turn may impact the capability of nearby inserts; inserts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Certain factors, including the fabrication techniques for the structure, the kind of structural design, and the type of materials used, can significantly alter the mechanical behavior of sandwich panel with cellular core. 9,10 In order to effectively utilize the AM method for sandwich structures, it is critical to comprehensively assess these factors and systematically perform rigorous evaluations of mechanical behavior, as highlighted in previous research. 11 Recent advances in AM technologies, including as selective laser melting (SLM) and fused deposition modeling (FDM), have made it possible to manufacture honeycomb structures with reduced feature and cell sizes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain factors, including the fabrication techniques for the structure, the kind of structural design, and the type of materials used, can significantly alter the mechanical behavior of sandwich panel with cellular core. 9,10 In order to effectively utilize the AM method for sandwich structures, it is critical to comprehensively assess these factors and systematically perform rigorous evaluations of mechanical behavior, as highlighted in previous research. 11 Recent advances in AM technologies, including as selective laser melting (SLM) and fused deposition modeling (FDM), have made it possible to manufacture honeycomb structures with reduced feature and cell sizes.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of these structures are a key factor in the development and manufacture of efficient sandwich structures. Certain factors, including the fabrication techniques for the structure, the kind of structural design, and the type of materials used, can significantly alter the mechanical behavior of sandwich panel with cellular core 9,10 . In order to effectively utilize the AM method for sandwich structures, it is critical to comprehensively assess these factors and systematically perform rigorous evaluations of mechanical behavior, as highlighted in previous research 11 …”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Stefan et al 14 estimated the out of plane shear modulus of honeycomb core by using the finite element. Soliman and Kapania 15 and Soliman 16 found the elastic properties of different shapes of honeycomb by using a detailed finite element model of representative unit cells applying the displacement approach and proposed empirical relations. Studies on the failure modes of sandwich composites can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%